Abundant mtDNA Diversity and Ancestral Admixture in Colombian criollo Cattle (Bos taurus) (2003)
ABSTRACT: Various cattle populations in the Americas (known as criollo breeds) have an origin in some of the first livestock introduced to the continent early in the colonial period (16th and 17th centuries). These cattle constitute a potentially important genetic reserve as they are well adapted to local environments and show considerable variation in phenotype. To examine the genetic ancestry and diversity of Colombian criollo we obtained mitochondrial DNA control region sequence information for 110 individuals from seven breeds. Old World haplogroup T3 is the most commonly observed CR lineage in criollo (0.65), in agreement with a mostly European ancestry for these cattle. However, criollo also shows considerable frequencies of haplogroups T2 (0.9) and T1 (0.26), with T1 lineages in criollo being more diverse than those reported for West Africa. The distribution and diversity of Old World lineages suggest some North African ancestry for criollo, probably as a result of the Arab occupation of Iberia prior to the European migration to the New World. The mtDNA diversity of criollo is higher than that reported for European and African cattle and is consistent with a differentiated ancestry for some criollo breeds.